(untitled) (Comprehensive Journal of Science, 2025)
This paper discusses the development of teaching reading comprehension for learners of English as a foreign or second language. Reading comprehension requires more than recognizing individual words; it involves connecting ideas across words, sentences, and larger textual units, as well as understanding the writer’s message. Reading is a fundamental skill in English language learning, as it enables students not only to decode written language but also to extract meaning and information from texts. The paper presents different views on reading comprehension, the major tasks involved in teaching reading, and the activities used in classroom instruction. Additionally, several effective strategies that can improve learners’ reading abilities are reviewed, along with the main approaches used in teaching reading.